A Hybrid Fuzzy Multicriteria Decision-Making Approach for Fighter Aircraft Selection: Application to the Algerian Air Force - Abdelghafour Kaanit; Kinza Nadia Mouss; Tarek Berghout (International Journal of Aerospace Engineering)
The selection of a fourth-generation fighter aircraft for the Algerian Air Force is a complex multicriteria decision-making (MCDM) process, marked by ambiguity and subjectivity. In the face of such challenges, the hybrid framework has applied the fuzzy analytic hierarchy process (fuzzy AHP), Shannon entropy, and fuzzy technique for order of preference by similarity to ideal solution. This approach utilizes linguistic variables represented by triangular fuzzy numbers to enhance adaptability and transparency in the decision-making process. Fuzzy AHP and entropy methods calculate the weights of selection criteria, while fuzzy TOPSIS ranks alternatives. The study is applied on a set of aircrafts, including SU-34, MIG-29, Rafale, and F-16, using technical and operational criteria such as range, autonomy, and climb rate. Results indicate that SU-34 is the optimal choice when using fuzzy AHP, while the F-16 ranks highest with the entropy method, with minimal score differences underscoring the precision and reliability of the methodology. This study overcomes traditional limitations, such as subjective bias and inflexibility, by leveraging fuzzy logic, enabling systematic assessments aligned with real-world constraints. The findings refine procurement decisions and provide a framework for balanced military evaluations. Future work may extend to advanced aircraft or unmanned systems.